Arctic Political Discourses : Constructing a Russian National Identity - Karlsen, Kristofer (Helsingfors universitet, 2016)
This research explores how Russian national identity is constructed through political discourses pertaining to the Arctic. Theoretically this thesis addresses how national identity is constructed through these discourses and subsequently how this identity is used to justify Russia’s Arctic policy to a domestic as well as an international audience. In order to achieve this a hybrid methodology combining critical discourse analysis and political discourse analysis was applied to two forms of political discourses; speeches by politicians and policy papers. This research has identified five discourses through which a Russian national identity is constructed and policy legitimised. These are international cooperation, security, governance, Russia as Arctic, and environment.